Estrategia de prevención y mediación familiar a partir de los componentes comunicacional y relacional de cinco familias que han vivido la experiencia de la conducta suicida en alguno de sus hijos(as) vinculados a un Colegio Parroquial de la Localidad de Kennedy - Carrascal Roso, Yoleida Patricia (Universidad Antonio Nariño, 2022)
The present work of investigation is called Strategy of prevention and family mediation in suicidal behavior; It arises from the cases of students reported to the Early Warning System of the District Secretary of Education during the years 2018,2019,2020; The objective is to generate a prevention and family mediation strategy based on the communicational and relational components of five families who have lived the experience of suicidal behavior in one of their children linked to a Parish College in the Locality of Kennedy. The methodological design approach is phenomenological-hermeneutical, the type of research is qualitative, with a descriptive scope.